2020
DOI: 10.21203/rs.3.rs-15599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of India’s national publicly funded health insurance scheme, Pradhan Mantri Jan Arogaya Yojana (PMJAY), in improving access and financial protection for hospital care: findings from household surveys in Chhattisgarh state

Abstract: Background:A national Publicly Funded Health Insurance (PFHI) scheme called Pradhan Mantri Jan Arogaya Yojana (PMJAY) was launched by government of India in 2018. PMJAY seeks to cover 500 million persons with an annual cover of around 7000 USD per household. PMJAY claims to be the largest government funded health scheme globally and has attracted an international debate as a policy for Universal Health Coverage. India’s decade-long experience of the earlier national and state-specific PFHI schemes had shown po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Mechanisms such as the biometric smart card, billing systems, and data reporting and sharing have not delivered on their promises nor led to greater accountability. More recent studies have indicated that these problems continue under the PMJAY [135]. Provider capture remains a central issue in the performance of PFHI-based policies to achieve UHC in the Indian context [136].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms such as the biometric smart card, billing systems, and data reporting and sharing have not delivered on their promises nor led to greater accountability. More recent studies have indicated that these problems continue under the PMJAY [135]. Provider capture remains a central issue in the performance of PFHI-based policies to achieve UHC in the Indian context [136].…”
Section: Discussionmentioning
confidence: 99%
“…The stated objectives of PMJAY are to reduce the nancial burden on poor and vulnerable groups for access to quality health services. However, the out-of-pocket expenditure and incidence of catastrophic health expenditure did not decrease with enrollment under PMJAY or other PFHI Schemes [16]. In the US, the We also found that SIMIS reduced OMISPR at the break point, and the treatment effect value was -0.0016, with self-payment decreasing by about 1.6%.…”
Section: Discussionmentioning
confidence: 65%
“…The stated objectives of PMJAY are to reduce the financial burden on poor and vulnerable groups for access to quality health services. However, the out-of-pocket expenditure and incidence of catastrophic health expenditure did not decrease with enrollment under PMJAY or other PFHI Schemes [16]. In the US, the Affordable Care Act (ACA) sought to protect families from high and rising health care expenditures by expanding health insurance coverage through the Medicaid program and reducing underinsurance through various avenues.…”
Section: Discussionmentioning
confidence: 99%